Dynamic Substitutes. A Semiotic Perspective - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2024)
In this article I aim at proving the relevance of a (possibly) new semiotic concept, which I termed dynamic substitute. In this regard, dynamic substitutes refer to those types of signs that manifest a kind of “dialectic relation” to the “things” they stand for; that is, they mutually influence each other during the transactions they are involved in. Not only words and money (as symbols), but also maps (as icons), constitute excellent examples of dynamic substitutes, as the American philosopher John Dewey suggested.